Sebuah Sintesis Pada Literatur: Strategi Intervensi Pemasaran Hijau Menuju Pembangunan Berkelanjutan (A Synthesis of Literature: A Green Marketing Intervention Strategy towards Sustainability Development) - Sri Widyastuti (JRB-Jurnal Riset Bisnis, 2019)
This paper describes the literature on green marketing intervention strategies in the framework of sustainable development with an emphasis on green marketing intervention strategies on the environmental problems facing the world today. The Sustainable Development Goals (SDGs) at the historic United Nations (UN) Summit has been officially enacted. For the next fifteen years, with this new universal target valid for all, the country will mobilize efforts to end all forms of poverty, fight inequality and overcome climate change. This study explains that both individuals and organizations can benefit from environmentally friendly marketing strategies. Public concerns over environmental damage in recent years have made marketers recognize the needs and marketing value of environmentally friendly. Attention to these conditions has changed the paradigm of the views of companies, marketers, and consumers to contribute to change towards goodness for nature itself. In today’s competitive business environment, profit-oriented and socially responsible companies have begun to adopt the concept of green marketing and address environmental issues as a source of competitive advantage. The disadvantages and future of green marketing interventions are also important reviews for future researchers. Thus at the same time can protect the environment to achieve sustainable development.